Human rights in Japan, South Korea and Taiwan - Neary, Ian (Routledge advances in Asia-Pacific studies., 2003)
This book looks in detail at the history of the introduction of human rights ideas into Japan, South Korea and Taiwan, and will be valuable to students and scholars of Asian Studies, Human Rights, Sociology and Politics.